Preparation of Polyamine Wheat Straw Cellulose for Adsorption of Cd(II) - Li, Jianqiang; Li, Daiqi; Pan, Qingshan; Chen, Xianlan; Shi, Ling; Yan, Heping; Zhou, Bo; Xu, Shijuan; Wang, Jing; Gou, Gaozhang; et al. (Asian Journal of Chemistry, 2015)
Wheat straw cellulose modified by diethylenetriamine was investigated as an adsorbent for removal of Cd(II) from aqueous solution. The preparing parameters on preparation of polyamine wheat straw cellulose were optimized. The effects of pH, adsorbent dose, contact time and initial concentration on the Cd(II) removal process were studied by using batch methods. The maximum adsorption capacity of adsorption of Cd(II) onto polyamine wheat straw cellulose was found to be 21.37 mg/g and the removal percentage was more than 90 %. The adsorption isotherms were analyzed using the Langmuir and Freundlich isotherms. The results showed that the adsorption process was well described by Langmuir isotherm model with correlation coefficients (R) of 0.9981 for adsorption of Cd(II).